Christology of the Old Testament ; v. 4 and a commentary on the Messianic predictions - Hengstenberg, Ernst Wilhelm, 1802-1869 (Edinburgh, Scotland T. and T. Calrk, 1858)
Contents : v. 4 : Messianic predictions in the prophets : The prophet Zechariah - The prophet Malachi - The New testament and the prophecies of Malachi. Appendices : Importance of the Messianic prophecies - Messianic expectations among the heathen - The divinity of the Messiah in the Old Testament - The suffering and atoning Christ in the Old Testament - History of the interpretqation of the Messianic prophecies - The nature of proophecy.
Keywords: Christology; Bible. O.T. -- Messianic prophecies